Digital storytelling and Co-creative Media: The role of community arts and media in propagating and coordinating population-wide creative practice - Woodrow, N.; Spurgeon, C.; Rennie, E.; Klaebe, H.; Heck, E.; Haseman, B.; Hartley, John; Edmond, M.; Burgess, J. (CULTURAL SCIENCE, 2015)
How is creative expression and communication extended among whole populations? What is the social and cultural value of this activity? What roles do formal agencies, community-based organisations and content producer networks play? Specifically, how do participatory media and arts projects and networks contribute to building this capacity in the contemporary communications environment?